Treatment of triple negative breast cancer by near infrared light triggered mild-temperature photothermal therapy combined with oxygen-independent cytotoxic free radicals. (August 2022) - Li, Ruihao; Hu, Xiaochun; Shang, Fangjian; Wu, Wenjing; Zhang, Haijun; Wang, Yixuan; Pan, Jiawei; Shi, Shuo; Dong, Chunyan
Abstract: Triple negative breast cancer (TNBC) is highly malignant and prone to recurrence and metastasis. Patients with TNBC usually have poor prognosis. Hence, it is urgent to develop new comprehensive treatments for TNBC. The combination of heat shock protein (HSP) inhibitor and the photothermal agent can reduce the temperature required to kill tumor cells, thus achieving mild-temperature photothermal therapy (PTT). Compared with traditional PTT, mild-temperature PTT not only decreases tumor thermoresistance introduced by the overexpression of HSP, but also reduces the damage to normal tissues. Meanwhile, Azo initiator 2, 2-azobis[2-(2-imidazolin-2-yl) propane]-dihydroch-loride (AIPH) can be thermally decomposed to generate oxygen-independent free radicals. Herein, a new therapeutic multifunctional nanoplatform (M-17AAG-AIPH) by loading heat shock protein 90 (HSP90) inhibitor (17AAG) and AIPH incorporated into mesoporous polydopamine (MPDA) was successfully constructed for mild-temperature PTT combined with oxygen-independent cytotoxic free radicals against TNBC. Under 808 nm laser irradiation, the mild-temperature PTT arising from the combined effects of 17AAG and MPDA induced a rapid release and decomposition of AIPH, promoting the apoptosis of cancer cells in hypoxic microenvironments. Both in vitro and in vivo results showed that the designed nanoplatform can significantly inhibit tumor growth and provided an efficient new therapeutic strategy for TNBC. Statement of significance: There is still an urgent need for new strategies for the treatment of triple negative breast cancer (TNBC). In this work, we successfully constructed a new therapeutic multifunctional nanoplatform (M-17AAG-AIPH) by co-carrying heat shock protein 90 (HSP90) inhibitor (17AAG) and AIPH on mesoporous polydopamine (MPDA). MPDA owned good biocompatibility and outstanding photothermal-conversion ability. The loading of 17AAG can reduce the heat resistance of tumor cells via specifically inhibiting the activity of HSP90, so as to achieve mild-temperature PTT. Meanwhile, 17AAG and MPDA mediated mild-temperature PTT promoted the decomposition of AIPH into oxygen-independent cytotoxic free radicals. Both in vitro and in vivo results showed that M-17AAG-AIPH can significantly inhibit tumor growth and provided an efficient new therapeutic strategy for TNBC. Graphcal abstract: Image, graphical abstract